Implementation of Active Knowledge Sharing Strategy in Intermediate Level Dokkai through Scientific Approach - Oktaviany, Feny; Philiyanti, Frida; Prasetio, Viana Meilani (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
This study aims to determine the effectiveness and to find out the advantages and disadvantages of the Active Knowledge Sharing strategy through a scientific approach in the Dokkai. In learning Japanese, learners often encountered difficulties in reading comprehension or Dokkai. Based on a questionnaire, the difficulties including reading kanji, followed by vocabulary competence and grammar competence. On the other hand, the time limitation in class cause problems of learning method which teacher rarely provide an introduction step to students in the form of questions or vocabulary exercises related to the reading material they will deal with. To overcome this problem, we need a learning strategy that emphasize the cooperative learning among students to achieve the objective of comprehending a reading. We chose the strategy initiated by Silberman (2013), namely Active Knowledge Sharing, as a good way to introduce students to the subject matter that will be learned. In addition, by monitoring how students solving each other's problems in team, teacher can evaluate how much knowledge they have. In this study a scientific approach is complemented to support the active learning in this strategy. The study conducted using an experimental method with pretest and posttest design. The sample are 38 students of fifth semester students who take Dokkai III course. Based on the analysis of research data, it found that the Active Knowledge Sharing strategy through a scientific approach is effective in learning Dokkai III. The advantages are that students who are initially passive become actively participate in learning and students can also answer the meaning of vocabulary without depending on dictionary or smartphones, and students are encouraged to help each other in solving problems which help students to comprehend the contents of reading easier and faster. However there are the disadvantages of this strategy such as inability to enhance student’s critical thinking and less suitable for students who are more focused if studying alone.